Traditional Chinese medicine phenomics research on glycolipid metabolism disorder: a review - Xinyi Fang; Linxuan Miao; Yanjiao Zhang; Yuxin Zhang; Runyu Miao; Huifang Guan; Jiaxing Tian (Digital Chinese Medicine)
Traditional Chinese medicine (TCM) has demonstrated unique advantages in the prevention and treatment of chronic diseases such as glycolipid metabolism disorder. However, its widespread application has been hindered by the unclear biological essence of TCM syndromes and therapeutic mechanisms. As an emerging interdisciplinary field, phenomics integrates multi-dimensional data including genome, transcriptome, proteome, metabolome, and microbiome. When combined with TCM's holistic philosophy, it forms TCM phenomics, providing novel approaches to reveal the biological connotation of TCM syndromes and the mechanisms of herbal medicine. Taking glycolipid metabolism disorder as an example, this paper explores the application of TCM phenomics in glycolipid metabolism disorder. By analyzing molecular characteristics of related syndromes, TCM phenomics identifies differentially expressed genes, metabolites, and gut microbiota biomarkers to elucidate the dynamic evolution patterns of syndromes. Simultaneously, it deciphers the multi-target regulatory networks of herbal formulas, demonstrating their therapeutic effects through mechanisms including modulation of insulin signaling pathways, improvement of gut microbiota imbalance, and suppression of inflammatory responses. Current challenges include the subjective nature of syndrome diagnosis, insufficient standardization of animal models, and lack of integrated multi-omics analysis. Future research should employ machine learning, multimodal data integration, and cross-omics longitudinal studies to establish quantitative diagnostic systems for syndromes, promote the integration of precision medicine in TCM and western medicine, and accelerate the modernization of TCM.